2022
DOI: 10.1039/d2ta00075j
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on Schottky sensors based on two-dimensional transition metal dichalcogenides

Abstract: 2D transition metal dichalcogenides (TMDs), such as MoS2, MoSe2, WS2, WSe2, etc. have unique physical, chemical, and mechanical properties and thus they are ideal sensing materials. 2D TMDs-based sensor have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 154 publications
0
30
0
Order By: Relevance
“…NO-2ads + 2NO-3ads → 3NO 2(gas) + O 2(gas) + e - (7) For NO gas, it is also an electron acceptor, and is easily oxidized into NO 2 gas in air.…”
Section: Sensors and Diagnostics Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…NO-2ads + 2NO-3ads → 3NO 2(gas) + O 2(gas) + e - (7) For NO gas, it is also an electron acceptor, and is easily oxidized into NO 2 gas in air.…”
Section: Sensors and Diagnostics Accepted Manuscriptmentioning
confidence: 99%
“…Recently, several reports have revealed that the emerging two-dimensional (2D) materials can make sensing response to toxic gases at low/room temperature, which not only solves the problem of high power consumption of traditional gas sensors to a certain extent, but also applies them to flexible wearable electronic devices to provide great convenience and achieve intelligent life. The 2D materials include reduced graphene oxide (rGO) 1 , transition metal dichalcogenides (TMDs) 2 , black phosphorus (BP) 3 , hexagonal boron nitride (h-BN) 4 , and transition metal carbides, nitrides and/or carbonitrides (MXene) 5 , which can be considered as the promising gas sensing materials owing to their unique single-atom layer structure that exhibits high specific surface area close to the theoretical extreme, excellent semiconductor performance, unique surface configurations with dangling bonds on the edge sites, and flexible basal planes [6][7][8][9][10] . Among them, The layered TMDs with the composition structure of MX 2 (M= Ti, Zr, Hf, V, Nb, Ta, Mo, W, Tc, Re, Pd, Pt and X= S, Se, Te) 11 have gained intensive attention in gas sensing materials because of their strong spin-orbit coupling interaction, tunable electronic, and the high interaction ability for the gas molecules adsorption 12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since gas sensors have widely penetrated every aspect of our daily lives, such as medical and food industries and environmental safety testing, 2D TMDs are ideal gas sensing materials due to their large specific surface-to-volume ratios, high sensitivity to adsorption of gases, which are available for interactions with gas molecules, abundant active sites to selectively bind gases, and good mechanical properties. As one of the most common air pollutants, NO x ( x = 1 and 2), which are mainly from the combustion of fossil fuels, are greatly harmful to the environment and human health such as the damage of human respiratory organs and nerves. , Therefore, the development and manufacture of highly sensitive and selective NO x gas sensors is a main challenge for monitoring air quality, especially, for the detection of NO x at parts per billion (ppb) levels for commercial applications in environmental monitoring and healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of graphene [ 1 ], more and more two-dimensional (2D) layered materials have been discovered [ 2 , 3 , 4 , 5 , 6 ]. Owing to their distinct electronic, optical, and thermoelectric performance, many studies have been devoted to boosting the practical applications of 2D materials [ 7 , 8 , 9 ]. Among these 2D materials, binary Ⅱ-Ⅵ zinc chalcogenides exhibit the potential for broad applications in optoelectronic and thermoelectric devices [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%